Leapfrogging? India's Information Technology Industry and the Internet - Miller, Robert R. (Washington, DC: World Bank and the International Finance Corporation, 2013)
The Internet has been seen by numerous observers, as a set of technologies that might enable developing countries to "leapfrog" over the development path, taken by industrial countries, enabling poorer countries to increase their rates of growth, and "catch up" sooner. Using India as a case study, this paper reviews the degree to which that promise might be realized. The paper concludes that while internet development in India is still at a very early stage in terms of numbers of connections, and overall use, the promise it offers for increased productivity, and economic growth, is likely to be significant. Most benefits are likely to come from business use of the internet for both internal control, and for dealing with business customers, not from customer use. In particular, global connections will be much enhanced by India's liberalized access to international internet gateways, and to privately-provided undersea cable access. This access alone could offer Indian companies, business opportunities that otherwise would flow to other, better connected Asian competitors. However, poor infrastructure, along with low public investment, remains a difficult problem to overcome. And, although technical education has been a bright spot, India's overall educational attainment is low in demographic terms, and illiteracy will critically limit "leapfrogging" the anticipated expansion of the internet. Rather, economic growth depends on complementary interactions between the private sector, and the government's adequate provision of public goods.